Redesain Tempat Pengelolaan Sampah Terpadu Pada Proyek Pembangunan Rumah Susun X Di Kota Y - Putri Dwi Yanti; Praditya Sigit Ardisty Sitogasa (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This research aims to identify the types and characteristics of waste generated from the X Flats Construction Project, evaluate waste management, redesign waste processing sites in accordance with applicable regulations. This research method involves data collection, observation, and interviews to determine the characteristics and volume of waste produced. Next, time calculations, packaging planning, and planning TPS area calculations are carried out. This includes adequate TPS capacity for each type of waste, selection of appropriate locations, as well as facilities such as storage tanks that meet the requirements, effective ventilation systems, adequate lighting, safe roof construction, availability of fire extinguishers, and appropriate transportation routes. in accordance. By taking into account all these aspects, it is hoped that the planned Integrated Waste Processing Site (TPST) can meet applicable regulatory standards